A self-assembled photoresponsive gel consisting of chiral nanofibers - Zou, Lei; Han, Dan; Yuan, Zhiyi; Chang, Dongdong; Ma, Xiang (Beilstein Journal of Organic Chemistry, 2018)
A novel compound based on a glutamic acid skeleton, containing azobenzene as a photoresponsive group and ureidopyrimidinone (UPy) as a connection site, was designed and synthesized. The monomer is capable of forming an organogel in nonpolar organic solvents and different types of nanostructures in other solvents. The state of the gel and the chirality of the nanostructures could both be adjusted by subsequent light irradiation at different wavelengths. The helical nanofiber-like morphology was verified in the internal structure of the gel. The performance of this gel was investigated by a series of methods, such as UV–vis absorption spectroscopy, circular dichroism, scanning electron microscopy and rheological techniques. This work provides a new method for facile synthesis of chiro-optical gels.
Keywords: chirality; nanostructure; organogel; photoresponse; self-assembly